A Lost Opportunity for Progressive Redistributionto Build Social Protection for All? Scenarios following emergency cash transfers in Central America - Martínez Franzoni, Juliana (2022)
The need for these policies is particularly urgent in Latin America, a region where policy responses to the pandemic, such as lockdowns and mobility restrictions to prevent the spread of the virus, immediately turned into a social and economic crisis. With 8 percent of the world's population but 30 percent of deaths from Covid-19 by mid-2021, Latin America is on the verge of going back at least a decade in terms of human development, poverty and inequality. But is the crisis simultaneously pushing for more progressive redistribution in this region and across the global South? Too often this question is answered based on normative claims or on the “politics of hope”: changes will happen because they are required and increasingly self-evident. Yet approaches based on good will and hope fail to illuminate the political economy constraints for transformative policies; they often stress the policies that ought to be implemented but not what needs to happen to actually put them in place. In this light, UNRISD´s call for a new eco-social contract would benefit from a political economic analysis of how to move in that direction.